Computation and Visualization of Regional-Scale Forest Disturbance and Associated Dissolved Nitrogen Export from Shenandoah National Park, Virginia - Keith N. Eshleman; Daniel A. Fiscus; Nancy M. Castro; James R. Webb; J Jr. Deviney (The Scientific World Journal)
Long-term watershed research conducted in Shenandoah National Park (SNP) in Virginia and elsewhere in the eastern U.S. indicates that annual export of dissolved nitrogen (N) from gaged forested watersheds to surface waters increases dramatically in response to vegetation disturbances. Dissolved N leakage is a common, well-documented response of small forested watersheds to logging in the larger region, while recent defoliation outbreaks of the gypsy moth (Lymantria dispar) larva in the deciduous forests of SNP have been shown to generate similar biogeochemical responses. A recent modeling analysis further suggests that a parsimonious, empirical, unit N export response function (UNERF) model can explain large percentages of the temporal variation in annual N export from a group of small gaged forested watersheds in the years following disturbance. The empirical UNERF modeling approach is completely analogous to the unit hydrograph technique for describing storm runoff, with the model representing annual N export as a linear deterministic process both in space and in time. The purposes of this analysis are to (1) test the applicability of the UNERF model using quarterly streamwater nitrate data from a group of ungaged watersheds in SNP; (2) demonstrate a park-wide application of a regional UNERF model that references the geographic distributions of bedrock geology and the timing and extent of gypsy moth defoliation over the entire SNP area; and (3) visualize the temporal and spatial patterns in vegetation disturbance and annual dissolved N export through the use of computer animation software. During water year 1992, the year of peak defoliation, our modeling study suggests that park-wide export had transiently increased by 1700% from a baseline rate of about 0.1 kg/ha/year. SNP forests appear to be characteristic of other N-limited second-growth forests in the eastern U.S. that leak little N under undisturbed conditions, despite receiving relatively large inputs of N from atmospheric deposition sources. Vegetation disturbances can apparently cause major changes in N input-output balances with potentially important ramifications for low-order forest streams and downstream receiving waters.